NON-PHILOLOGICAL HIGHER EDUCATION PROGRAMS: SPECIFIC FEATURES, PEDAGOGICAL CHALLENGES, AND LINGUISTIC COMPETENCE DEVELOPMENT - Dilnoza Botirovna Rakhimova (Bright Mind Publishing, 2025)
The article examines the specific features of non-philological higher education programmes and their implications for the development of students’ linguistic and communicative competences. In programmes such as engineering, information technology, medicine, architecture and economics, language is not the central object of study, yet it functions as an essential mediating tool for acquiring disciplinary knowledge and participating in professional communication. Drawing on the frameworks of English for Specific Purposes (ESP), Content and Language Integrated Learning (CLIL), competency-based education and constructivist pedagogy, the study explores how curriculum design, didactic organisation, assessment systems and digital learning environments shape the status of language subjects in non-philological contexts.
Keywords: Non-philological education, English for Specific Purposes (ESP), CLIL, curriculum design, competency-based learning, professional communication, disciplinary literacy, higher education.